1999
DOI: 10.1046/j.1365-2656.1999.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Gyrfalcon predation on ptarmigan: numerical and functional responses

Abstract: Summary1. Gyrfalcon predation on ptarmigan during the breeding season was studied in north-east Iceland 1981±97. The ptarmigan population went through a complete 10-year cycle of numbers with a 4´3-fold dierence in density between high and low years. The yearly number of occupied gyrfalcon territories was correlated with ptarmigan density with a 3-year time-lag. Total falcon numbers in late summer (territorial adults +¯edglings) showed a 2-year lag with ptarmigan numbers. Variability in falcon density was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
111
4
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 52 publications
7
111
4
3
Order By: Relevance
“…When ptarmigan were relatively scarce, non-laying, delayed nesting, and clutch desertions were common. These observations were consistent with those of other studies (see Nielsen 1999).…”
supporting
confidence: 94%
“…When ptarmigan were relatively scarce, non-laying, delayed nesting, and clutch desertions were common. These observations were consistent with those of other studies (see Nielsen 1999).…”
supporting
confidence: 94%
“…In Iceland, for example, Nielsen (1999Nielsen ( , 2003 has shown that the proportion of pairs starting to breed depends on the density of the Rock Ptarmigan. The decline of Willow Ptarmigan and Rock Ptarmigan populations have been evaluated as the most worrying threats to the Gyrfalcon in northern Europe, together with lack of secure nest sites, according to the official Gyrfalcon Action Plan of the European Union (Koskimies 1999(Koskimies , 2006a.…”
mentioning
confidence: 99%
“…In Europe, research on this topic has been most intensive so far in Iceland (Bengtson 1971, Nielsen and Cade 1990, Nielsen 1999, 2003, but there are important publications also from Norway (Hagen 1952, Langvatn 1977, Langvatn and Moksnes 1979, from Sweden (Lindberg 1983, Nyström et al 2005, and from the Kola Peninsula, Russia (Dementiev and Gortchakovskaya 1945, Kishchinskiy 1958, Giljazov et al 2008). In the New World, diet of the Gyrfalcon has been studied in Greenland (Burnham andMattox 1984, Booms andFuller 2003), Canada (Poole and Boag 1988) and Alaska (Cade 1960).…”
mentioning
confidence: 99%
See 2 more Smart Citations